Correction to the Resolution Equation for Micellar Electrokinetic Capillary Chromatography for Various Cases - Ghowsi, Kiumars; Ghowsi, Hosein (Asian Journal of Chemistry, 2011)
A new model based on effective length migrated on a similar to tread mill case for various modes of operation in capillary zone electrophores was constructed. In present work similar treatment has been applied to micellar electrokinetic capillary chromatography and new equations obtained for the number of theoretical plates and resolution equations.